ダイ 27 ジ ナンキョク チイキ カンソク タイ キショウ ブモン ホウコク 1986 - 手塚, 正一; テヅカ, マサイチ; 渡部, 信行; ワタナベ; 坂尻, 政市; サカジリ, マサイチ; 佐々木, 洋; ササキ, ヒロシ; Tezuka, Masaichi; Watanabe, Nobuyuki; Sakajiri, Masaichi; Sasaki, Hiroshi (1989)
P(論文) この報告は, 第27次南極地域観測隊越冬隊気象部門が, 1986年2月1日から1987年1月31日までの1年間, 昭和基地において実施した地上および高層気象観測の結果をまとめたものである。 This paper describes the result of meteorological observations (mainly surface and aerological) at Syowa Station from February 1,1986 to January 31,1987. Observation items and methods are almost the same as in 1985. departmental bulletin paper